2020
DOI: 10.3390/ijms21218117
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Understanding TKS4 and TKS5: Molecular Scaffolds Regulating Cellular Processes from Podosome and Invadopodium Formation to Differentiation and Tissue Homeostasis

Abstract: Scaffold proteins are typically thought of as multi-domain “bridging molecules.” They serve as crucial regulators of key signaling events by simultaneously binding multiple participants involved in specific signaling pathways. In the case of epidermal growth factor (EGF)-epidermal growth factor receptor (EGFR) binding, the activated EGFR contacts cytosolic SRC tyrosine-kinase, which then becomes activated. This process leads to the phosphorylation of SRC-substrates, including the tyrosine kinase substrates (TK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 192 publications
1
28
0
Order By: Relevance
“…The molecular mechanism for Tks5-driven podosome formation has been previously described in other cell types, and chances are that similar processes take place in myotubes [ 39 ] ( Figure 4 D). Tks5 is initially phosphorylated by non-receptor tyrosine kinase, c-SRC, and is recruited to the cell membrane by an adaptor protein GRB2, which has been also shown to interact with αDB1 in the muscle, where it is required for AChR organization [ 21 , 28 , 40 ].…”
Section: Discussionmentioning
confidence: 53%
“…The molecular mechanism for Tks5-driven podosome formation has been previously described in other cell types, and chances are that similar processes take place in myotubes [ 39 ] ( Figure 4 D). Tks5 is initially phosphorylated by non-receptor tyrosine kinase, c-SRC, and is recruited to the cell membrane by an adaptor protein GRB2, which has been also shown to interact with αDB1 in the muscle, where it is required for AChR organization [ 21 , 28 , 40 ].…”
Section: Discussionmentioning
confidence: 53%
“…Invadopodia are actin-rich protrusions of the basolateral plasma membrane and are associated with degradation of the extracellular matrix in cancer invasiveness and metastasis [ 16 , 17 ]. Previous studies have revealed that invadopodia are composed of structural proteins, such as cortactin, TKS4, and TKS5 [ 18 20 ], and are regulated by numerous regulatory proteins that control actin dynamics [ 21 ]. EMT-related genes, such as TWIST1, and Rho GTPases, such as RAC/CDC42, reportedly play important roles in invadopodia formation [ 22 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both Tks4 and Tks5 have roles in cell motility by affecting the formation of podosomes and invadopodia [ 13 , 15 , 16 ]. However, despite the structural similarities, their functions are not totally overlapping [ 15 , 17 ]. In Src-transformed fibroblasts, only Tks4 recruits membrane type-1 matrix metalloproteinase to podosomes, thus playing a role in extracellular matrix degradation in these migrating cells [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Upon phosphorylation, Tks4 translocates to the plasma membrane where it binds phosphatidylinositol lipids via its PX domain. Membrane-anchored Tks4 can then interact with other signaling molecules [ 17 ]. The cytosol-to-cell membrane translocation of signaling molecules is a widespread regulatory mechanism in signal transduction [ 4 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%